2015
DOI: 10.1080/21645515.2015.1045167
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective pooled analysis assessing the effect of age on the immunogenicity ofHavrix™ in healthy adults

Abstract: Over recent decades, the global incidence of hepatitis A virus infection has been reduced by improvements in sanitation infrastructure and through immunization programs. The immunogenicity and field efficacy of the inactivated hepatitis A vaccine (Havrix TM , GSK, Belgium) has been demonstrated in clinical trials, population-impact studies as well as in several outbreak settings. However, immunological data in older populations are limited, with only few studies assessing the immune response of this vaccine in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
(54 reference statements)
0
7
0
1
Order By: Relevance
“…whether or not these often weak and slow responding subjects would profit from two primary doses (4 weeks apart), 29 , 114 especially when protection is needed speedily prior to traveling. This issue has been contested in a retrospective analysis of pooled study data, 186 even so 20.3% of ≥ 40 year old healthy subjects were two weeks after one dose not seroprotected (≥20 mIU/mL). In addition, it should be investigated if following waning of measurable antibodies after >10 years the immune memory is still intact or whether elderly and/or immunocompromised subjects would routinely need a late second booster dose.…”
Section: Emerging Issues and Areas For Researchmentioning
confidence: 99%
“…whether or not these often weak and slow responding subjects would profit from two primary doses (4 weeks apart), 29 , 114 especially when protection is needed speedily prior to traveling. This issue has been contested in a retrospective analysis of pooled study data, 186 even so 20.3% of ≥ 40 year old healthy subjects were two weeks after one dose not seroprotected (≥20 mIU/mL). In addition, it should be investigated if following waning of measurable antibodies after >10 years the immune memory is still intact or whether elderly and/or immunocompromised subjects would routinely need a late second booster dose.…”
Section: Emerging Issues and Areas For Researchmentioning
confidence: 99%
“…The effectiveness of vaccination is high and concerns both a pre-and post-exposure prophylaxis. There have been reports that confirm obtaining of a high titre of anti-HAV IgG antibodies in patients <40 years old faster after the first dose of vaccination, indicating at the same time a satisfactory immune response in older patients (11,12). The effectiveness of inactivated hepatitis A vaccines has been confirmed in vaccination programs, among other countries, in Israel, where vaccination included children aged 18 months (first dose) and 24 months (booster).…”
Section: By 1977 the Highest Incidence Of Hepatitis A Inmentioning
confidence: 92%
“…Istnieją doniesienia, które potwierdzają szybsze osiąganie wysokiego miana p/ ciał anty-HAV IgG u pacjentów < 40 r.ż. po I dawce szczepienia, zwracając jednocześnie uwagę na osiągnięcie zadowalającej odpowiedzi immunologicznej u pacjentów starszych (11,12). Efektywność inaktywowanych szczepionek przeciwko wzw A potwierdzono w programach szczepień m.in.…”
Section: By 1977 the Highest Incidence Of Hepatitis A Inunclassified
“…A retrospective pooled analysis assessing the effect of age on the immunogenicity of the inactivated HAV vaccine in healthy adults according to randomized, double-blind vaccination studies, concluded that the immune response was similar in adults aged >40 y and in those aged 20-30 y one month after the first and second dose, whereas younger subjects had a higher seroconversion rate 15 d after the first dose. 38 The prevalence of anti-HAV in the population has been decreasing, raising concerns that anti-HAV levels in IG preparations might lessen effective levels. Although there is no standard for antibody levels in IG preparations, reduced anti-HAV titers have been documented in pooled plasma in the United States and Europe.…”
Section: Discussionmentioning
confidence: 99%